THE NON-EXECUTABLE CIVIL DECISION: WILL THEY GET LEGAL CERTAINTY? - Adiasih, Ning; Kirana, Gandes Candra; Rustamovich, Ehsonov Jasurbek (UNISSULA, 2024)
The aims of this research is to analyze the basis for judges' considerations in issuing non-executory civil case decisions and to analyze the legal consequences that arise after the civil case decision is declared unexecutable. This legal research is a type of normative or doctrinal research that is descriptive analytical in nature. The results of this study are that non-executory reasons are not directly regulated in the HIR/Rbg, these reasons are regulated in Book II, Edition 2013: Technical Guidelines for Administrative Courts and Technical Courts for General and Special Civil Courts. The legal consequences of civil case decisions that are declared unexecutable by the Court judge because the execution must be stopped on the grounds of error in objecto. The novelty in this writing is that a decision that contains an error in the object that causes the decision to lose its enforceable power, then based on Article 231 RBg, the judge must order the execution seizure of the land on which the execution order is placed to be revoked and then its status returned to its original state.